Analisis Strategi Pemasaran Usaha Mikro Kecil dan Menengah Rumah Makan Padang di Desa Patumbak Kampung Kecamatan Patumbak - Hokber Yenerson Nainggolan; Abdul Malik (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
This study aims to determine the analysis of the marketing strategy of micro, small and medium businesses at Padang restaurants in Patumbak Kampung Village, Patumbak District through 4p marketing mix analysis, segmentation, targeting and positioning. This study uses a SWOT approach, aiming to determine the marketing strategy of micro, small and medium enterprises at Padang restaurants in Patumbak Kampung Village, Patumbak District. The analysis technique used is SWOT analysis. Based on the SWOT analysis, it can be concluded that for Putri Minang Restaurant the strength-opportunity (SO) strategy includes increasing superior products. The strength-threat (ST) strategy includes determining the price according to the quality of the food. Weakness-opportunity (WO) strategy includes improving service quality. Weakness-threat (WT) strategy, includes establishing good relationships with customers. For Ridho Restaurant, the strength-opportunity (SO) strategy includes maintaining service quality. Strength-threat (ST) strategy, which includes creating a distinctive character. Weakness-opportunity (WO) strategy, includes making better promotions and developing human resources. Weakness-threat (WT) strategy, includes improving the quality of food. For Pituah Mandeh Restaurant, the strength-opportunity (SO) strategy includes giving trust to consumers. Strength-threat (ST) strategy, which includes maintaining price and product availability. Weakness-opportunity (WO) strategy includes using promotions to attract consumers. Weakness-threat (WT) strategy includes developing promotional strategies, maintaining product quality, paying attention to service quality and increasing competitiveness. Keywords: Marketing Strategy, UMKM